1999
DOI: 10.1002/jlb.66.3.471
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 knock-out mice exhibit resistance to splanchnic artery occlusion shock

Abstract: We used IL-6 knock-out (KO) mice to evaluate a possible role for IL-6 in the pathogenesis of splanchnic artery occlusion shock (SAO). SAO shock was induced by clamping both the superior mesenteric artery and the celiac trunk, followed by release of the clamp. There was a marked increase in the peroxynitrite formation in the plasma of the SAO-shocked IL-6 wild-type (WT) mice after reperfusion. Immunohistochemical examination demonstrated a marked increase in the immunoreactivity to nitrotyrosine in the necrotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
43
0
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 46 publications
4
43
0
4
Order By: Relevance
“…These include stimulation of neutrophil release from the bone marrow (32), prevention of neutrophil apoptosis (33), activation of neutrophils to produce toxic enzymes (34), and activation of endothelial cells to express intercellular adhesion molecule 1 and chemokines (35,36). These effects of IL-6 are confirmed by the decreased inflammatory response in transgenic knockout mice after ischemia in the lung (37), gut (7,38), or brain (6); after injections of sterile turpentine (39) or carrageen (35); and after infections. (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…These include stimulation of neutrophil release from the bone marrow (32), prevention of neutrophil apoptosis (33), activation of neutrophils to produce toxic enzymes (34), and activation of endothelial cells to express intercellular adhesion molecule 1 and chemokines (35,36). These effects of IL-6 are confirmed by the decreased inflammatory response in transgenic knockout mice after ischemia in the lung (37), gut (7,38), or brain (6); after injections of sterile turpentine (39) or carrageen (35); and after infections. (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Cuzzocrea et al (8) reported that gut mucosal inflammation and histological damage were markedly attenuated in IL-6 Ϫ/Ϫ compared with IL-6 ϩ/ϩ mice subjected to splanchnic artery occlusion and reperfusion. In another study (9), the same laboratory showed that intestinal inflammation induced by intraperitoneal administration of zymosan was decreased in IL-6 Ϫ/Ϫ compared with IL-6 ϩ/ϩ mice.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, these 2 pathways are overrepresented at 3 hours, subsequent to the spike of Il6 at 1 to 3 hours, supporting the hypothesis that Il6 up-regulation is an early and important phenomenon in isoproterenol-induced cardiotoxicity. However, other genes reported to have important roles in acute myocardial The data represent the mean fold difference of isoproterenol-treated rats (n = 4-5/timepoint) compared to water-treated rats (n = 3 rats/time point Indeed, the effects of Il6 on myocardial function are still under debate: several lines of evidence suggest that Il6 has detrimental effects on the damaged heart, because animals injected with anti-Il6 antibodies have reduced inflammation in several models of ischemia (Cuzzocrea et al, 1999;Kukielka et al, 1995) and Il6-KO mice have fewer histologic lesions and/or better survival than wild-type mice in some inflammatory models (Cuzzocrea et al, 1999;Eriksson et al, 2003). Yet, other studies support a protective function of Il6 in the myocardium, because cardiomyocyte-restricted Il6-KO mice are more susceptible to myocardial injury caused by doxorubicin or lipopolysaccharides (Jacoby et al, 2003) and because mediators that, similarly to Il6, bind to Il6st favor cardiomyocyte hypertrophy and survival (Yasukawa et al, 2001).…”
Section: Interleukin 6 Pathwaymentioning
confidence: 99%